Effect of temperature on inversion concentration of NO2 differential absorption lidar and optimized algorithm - Liu, Qiuwu; Chen, Yafeng; Yang, Jie; Jian, Huang; Hu, Shunxing (Journal of quantitative spectroscopy & radiative transfer, 2022)
•The absorption cross section of nitrogen dioxide changes with the change of temperature, which will affect the concentration inversion of nitrogen dioxide differential absorption lidar.•The temperature decreases with the increase of altitude, so the absorption cross section of nitrogen dioxide must be corrected in the concentration inversion.•It is generally considered that the temperature is constant in horizontal detection, but the temperature is different in different seasons or different times of the day, so the absorption cross section of nitrogen dioxide must be corrected.•Therefore, when using differential absorption lidar to detect the concentration of nitrogen dioxide in the atmosphere, whether it is horizontal or vertical detection, the absorption cross section must be corrected. A differential absorption lidar (DIAL) for measurement of atmospheric nitrogen dioxide (NO2) concentration is developed based on atmospheric backscattered signals. Two Nd:YAG lasers are used to pump into two dye lasers to produce two wavelengths λon (448.1 nm) and λoff (446.6 nm), respectively. The NO2 absorption cross section varies with the change of ambient temperature. The changes of NO2 absorption cross section and the influence of inversion concentration are analyzed. The results show that when the horizontal profile is measured with the absorption cross section at room temperature of 20 °C as the reference value, the relative error of 1% can be caused by the temperature change of 1 °C. In vertical profile measurement, on the ground below 3 km, every 100 m increase in altitude can bring a relative error of 0.6%. By correcting the absorption cross section affected by temperature, the relative error of the measured concentration is less than 5%.On this basis, the experimental observation of atmospheric NO2 concentration profiles was carried out, and errors induced by temperature change were corrected. The experimental results show that the system is stable and reliable, and the temperature correction algorithm is effective.